Inovasi Mal Pelayanan Publik Dalam Meningkatkan Kualitas Pelayanan Publik Di Kota Samarinda - Fatwa Indah Rahayu; Muhammad Noor; Muhammad Jamal Amini (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to describe as a whole the Public Service Mall Innovation in Improving the Quality of Public Services in Samarinda City by paying attention to the success of innovation based on the characteristics of innovation, according to Rogers in Nurdin (2019), namely: Relative Advantage, Combability, Complexity (Complexity), Triability (Probability of Trying), and Observability (Ease of Observation). As well as identifying inhibiting factors and supporting factors. The results of the study show that the Relative Advantages of Public Service Malls have integrated services in the same building, thus saving costs, time and effort as well as online queues. While the economic advantage is only services with regional retribution provisions. The presence of the Public Service Mall Innovation is in accordance with the rules and needs of the community. The level of complexity is in the form of policy mechanisms and procedures from each agency, the internet is not maximal, there is only one elevator, and the counters are slow to open. Samarinda City Public Service Mall does not conduct trials and socialization only on social media. This Public Service Mall innovation is easy for the public to observe and every counter provides IKM. The agency with the most types of services is DPMPTSP. Meanwhile, the agency with the fewest services is Baznas. The inhibiting factors are inter-agency coordination and budget constraints. While the supporting factors are adequate facilities and infrastructure, capable human resources, and support from the local government.